Alcohol Use and Risk Factors for Sexual Aggression: Differences According to Relationship Status - Norona, Jerika C. (Journal of interpersonal violence, 2021)
The present study examined the ways alcohol use and risk factors for sexual assault perpetration vary by relationship status. Participants included 242 college men (age = 18-22 years) from a northeastern university who identified as being single or in a casual or committed dating relationship with a female partner. ANCOVAs and paired t tests compared individuals who were single, casually dating, and in committed relationships on self-reported alcohol use during sexual situations, beliefs about sexual communication, behavior associated with sexual aggression, and peer approval of sexual aggression. Differences in alcohol use during sexual situations and behavior associated with sexual aggression according to relationship status emerged. Post hoc analyses examining whether alcohol use during sexual situations moderated significant associations between relationship status and behavior associated with sexual aggression suggested that men in committed relationships who endorsed more frequent alcohol use during sexual situations also endorsed more behavior associated with sexual aggression. Findings suggest that individuals in committed relationships who often use alcohol during sexual situations may be at increased risk of sexually aggressive behavior.